Democratization, sequencing, and state failure in Africa: lessons from Kenya - Branch, D; Cheeseman, N (Oxford University Press, 2008)
In order to complement ongoing current empirical research, this article draws wider lessons from the crisis that grew out of the disputed Kenyan presidential election of December 2007. Looking beyond the immediate trigger for the subsequent violence - namely, the election itself - the paper instead locates the roots of the crisis within three historical trends: elite fragmentation, political liberalization, and state informalization. The origins of each can be traced to the style of rule employed by Daniel arap Moi. Even though his first government of 2002-5 perpetuated these trends, President Mwai Kibaki failed to recognize their implications for national unity and the exercise of power in 2007. The article then addresses the sequencing debate within the literature on democratization, identifying the lessons that can be taken from the Kenyan case for other states. Kenya has shown again that political liberalization is a high-risk activity that can produce unintended side-effects. Drawing on examples from other African states, we argue that the processes of democratization and reform can be undertaken simultaneously, but that this twin-tracked approach requires institutional reforms not yet undertaken by a large number of African polities.